2022
DOI: 10.1111/anae.15627
|View full text |Cite
|
Sign up to set email alerts
|

Delirium and COVID‐19: a narrative review of emerging evidence

Abstract: Delirium is a common condition affecting hospital inpatients, including those having surgery and on the intensive care unit. Delirium is also common in patients with COVID-19 in hospital settings, and the occurrence is higher than expected for similar infections. The short-term outcomes of those with COVID-19 delirium are similar to that of classical delirium and include increased length of stay and increased mortality. Management of delirium in COVID-19 in the context of a global pandemic is limited by the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 77 publications
1
11
0
Order By: Relevance
“…Neurocognitive dysfunction and damage after COVID infection are also common. 31 , 32 , 33 , 34 , 35 , 36 Delirium is a well-recognized complication of COVID and is associated with a poor prognosis and increased mortality. While specific post-COVID perioperative neurocognitive complications are not yet reported, we remain highly concerned about the risk of postoperative delirium and other postoperative neurocognitive disorders.…”
Section: Mechanism Of Perioperative Risk and Areas Of Uncertaintymentioning
confidence: 99%
“…Neurocognitive dysfunction and damage after COVID infection are also common. 31 , 32 , 33 , 34 , 35 , 36 Delirium is a well-recognized complication of COVID and is associated with a poor prognosis and increased mortality. While specific post-COVID perioperative neurocognitive complications are not yet reported, we remain highly concerned about the risk of postoperative delirium and other postoperative neurocognitive disorders.…”
Section: Mechanism Of Perioperative Risk and Areas Of Uncertaintymentioning
confidence: 99%
“…34 As the SARS-CoV-2 demonstrates an ability to invade the CNS and provoke immune responses, the challenge lies in discerning whether the neurological manifestations are primarily a consequence of direct viral effects or an intricate interplay between the virus and the host's immune system. 35,36…”
Section: Neurological Manifestations Of Covid-19mentioning
confidence: 99%
“…The heterogeneity in neurological manifestations observed in Covid‐19 patients prompts a deeper exploration into the underlying molecular and cellular processes 34 . As the SARS‐CoV‐2 demonstrates an ability to invade the CNS and provoke immune responses, the challenge lies in discerning whether the neurological manifestations are primarily a consequence of direct viral effects or an intricate interplay between the virus and the host's immune system 35,36 …”
Section: Neurological Manifestations Of Covid‐19mentioning
confidence: 99%
“…Patients with postoperative delirium have an increased risk of developing other postoperative complications, hospital readmission, and a higher healthcare-associated cost and mortality rate than those without delirium [ 9 , 10 , 11 ]. Precipitating factors of postoperative delirium include age, duration of surgery, the extent of surgery, and perioperative medication administration, such as high doses of opioids and benzodiazepines [ 12 , 13 , 14 ]. However, patients with a diminished brain reserve, such as those with dementia, also have an increased risk for postoperative delirium [ 7 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Precipitating factors of postoperative delirium include age, duration of surgery, the extent of surgery, and perioperative medication administration, such as high doses of opioids and benzodiazepines [ 12 , 13 , 14 ]. However, patients with a diminished brain reserve, such as those with dementia, also have an increased risk for postoperative delirium [ 7 , 14 , 15 ]. Studies have shown Alzheimer’s disease-like features in patients with a history of long COVID, suggesting permanent brain damage [ 16 ].…”
Section: Introductionmentioning
confidence: 99%